Body Mass Index and Disease Activity Are Associated With Moderate to Severe Disability in Crohn's Disease: A Cross-Sectional Study in Shanghai - Bian, DongSheng; Jiang, Yongmei; Gu, Yubei; He, Zirui; Chen, Qi; Tang, Yonghua; Zhong, Jie; Shi, Yongmei (Frontiers in Medicine, 2021)
Background: The inflammatory bowel disease disability index (IBD-DI) was used to access body functional consequences and disease burden. However, Chinese population data are considerably limited. Objective: We aimed to screen for disability in patients with Crohn’s disease (CD) and to assess potential associations with clinical parameters as well as indices related to sarcopenia. Methods: This cross-sectional study includes 146 CD patients from Ruijin Hospital in Shanghai, China. All patients were screened for disability and sarcopenia on the basis of the IBD-DI scale, and the criteria for Asian Working Group for Sarcopenia, respectively. Clinical and demographic variables were collected. Results: Approximately 52.05% of the subjects suffered from moderate or severe disabilities. The prevalence of sarcopenia (48.68% vs. 31.43%, P=0.043), Patient-Generated Subjective Global Assessment score or PG-SGA≥ 4 (39.47% vs. 17.14%, P=0.003), and high-level C- reactive protein (27.63% vs. 11.43%, P=0.021) were higher in patients with moderate to severe disability than in those without to minimal disability. By multivariate regression modeling, the following were identified as independent factors related to moderate to severe disability: disease activity (OR:10.47, 95% CI: 2.09 to 52.42) and body mass index (BMI) (OR:4.11, 95% CI: 1.80 to 9.38). Conclusions: Disability is common in CD patients. Our study showed that moderate to severe disability is not directly associated with muscle mass or muscle quantity but is mostly correlated with disease activity as well as BMI. Thus, close monitoring and follow-up should be conducted on patients who are at high risk of disability, and effective measures should be taken, which may be the best way to prevent disability and help patients return to normal life.